CAN CORPORATE SUSTAINABILITY PERFORMANCE (CSP) OVERCOME INDONESIA'S CORPORATE DEBT PROBLEMS? - Febrian, Johnson Ferry; Hendriyeni, Nora Sri (Jurnal Akuntansi dan Keuangan Indonesia, 2024)
Based on IMF publications (2022), Indonesian companies have a risky debt level that may cause bankruptcy, so companies are required to make leverage adjustments to return the debt to its optimal level. In recent years, corporate sustainability performance (CSP) practices have been proven to improve performance and overcome financial problems such as debt by integrating sustainability aspects into business processes. Based on stakeholder theory and trade-off theory, this study aims to examine the effect of CSP on leverage adjustment and the role of competitive advantage, equity mispricing, profitability, and firm size in moderating this relationship. This study used a sample of 40 listed companies that registered on the Indonesia Stock Exchange and implemented CSP from 2019 to 2022. By using multiple linear regression analysis and moderated regression analysis, this study shows that companies with CSP can increase company leverage adjustments. Meanwhile, company characteristics such as equity mispricing and company size have proven to strengthen this relationship, but competitive advantage and profitability do not influence it. The results of this study provide theoretical and practical benefits by enhancing knowledge about CSP and leverage adjustments, as well as enabling managerial and regulatory parties to make the right decisions.